2023
DOI: 10.1038/s41598-023-38612-w
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia by intravenous propofol reduces the incidence of intra-operative gastric electrical slow-wave dysrhythmias compared to isoflurane

Abstract: Gastric motility is coordinated by bioelectrical slow-wave activity, and abnormal electrical dysrhythmias have been associated with nausea and vomiting. Studies have often been conducted under general anaesthesia, while the impact of general anaesthesia on slow-wave activity has not been studied. Clinical studies have shown that propofol anaesthesia reduces postoperative nausea and vomiting (PONV) compared with isoflurane, while the underlying mechanisms remain unclear. In this study, we investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…21 A recent study in pigs demonstrated disruption of gastric slow wave activity with isoflurane anesthesia, and a decrease in frequency and velocity of the slow wave, as compared to under propofol anesthesia. 11 However, this study and another examining the effects of anesthesia (thiopentone, nitrous oxide, and isoflurane) on gastric slow wave activity in the porcine model did not include a direct comparison to the awake condition. 6 While there was a stark change in signal power between the anesthetized and awake states, it is important to acknowledge that animal behavioral movement itself could have contributed to the observed difference in signal power between the awake and isoflurane anesthesia conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…21 A recent study in pigs demonstrated disruption of gastric slow wave activity with isoflurane anesthesia, and a decrease in frequency and velocity of the slow wave, as compared to under propofol anesthesia. 11 However, this study and another examining the effects of anesthesia (thiopentone, nitrous oxide, and isoflurane) on gastric slow wave activity in the porcine model did not include a direct comparison to the awake condition. 6 While there was a stark change in signal power between the anesthetized and awake states, it is important to acknowledge that animal behavioral movement itself could have contributed to the observed difference in signal power between the awake and isoflurane anesthesia conditions.…”
Section: Discussionmentioning
confidence: 97%
“…10 Moreover, at least one study reported that general anesthesia suppresses GI slow wave responses, and another recent study demonstrated more slow wave dysrhythmia with inhaled isoflurane anesthesia than intravenous propofol. 7,11 The current study was designed to determine the effects of isoflurane anesthesia on gastric myoelectric signals. The ferret was used in this study because it is a well-known model for emetic testing and GI measures, 3,[12][13][14] and importantly, nausea and vomiting are cardinal features of gastroparesis.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this method is that smooth muscle function may be affected by anesthesia. It has been found that gastrointestinal motility can be impaired by application of general anesthetics such as isoflurane, via disruption of cholinergic mechanisms 47 , 48 . Care should be taken when determining the manner of anesthesia for future experiments, and consideration as to possible effects of anesthesia on smooth muscle function, and how this may affect results.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this method is that smooth muscle function may be affected by anesthesia. It has been found that gastrointestinal motility can be impaired by application of general anesthetics such as iso urane, via disruption of cholinergic mechanisms 41,42 . Care should be taken when determining the manner of anesthesia for future experiments, and consideration as to possible effects of anesthesia on smooth muscle function, and how this may affect results.…”
Section: And Future Applicationsmentioning
confidence: 99%